How many daily steps are really enough for adolescents? A cross-validation study (¿Cuántos pasos diarios son realmente suficientes para los adolescentes? Un estudio de validación cruzada) - Parra Saldías, Maribel; Mayorga-Vega, Daniel; López-Fernández, Iván; Viciana, Jesús (Retos, 2018)
The main purpose of the present study was to compare the accuracy of total daily steps thresholds associated to the recommended 60 min per day moderate-to-vigorous physical activity in adolescents. A total of 156 adolescents, 87 males and 69 females, participated in the present study. Objectively-measured moderate-to-vigorous physical activity and steps were assessed by GT3X accelerometers for eight consecutive days. The accuracy of the following total daily steps thresholds was calculated (males/females): 9,930, 11,714, 12,000, 11,000/10,500, 14,000/11,500, 13,000/12,000, 8,500/7,500, 11,500/9,000, 10,500/9,500, 12,118, 12,118/12,605, and 10,000. The results of accuracy both uncensored and censored total daily steps cut-off points ranged from low to high. For the uncensored total daily steps, the cut-off 11,000 for males and 10,500 for females showed the best results: Sensitivity = .85; Specificity = .94; Youden’s index = .78; Proportion of agreement = .93, and Kappa coefficient = .67, p < .001. For the censored total daily steps, the 10,000 cut-off score showed the best results: Sensitivity = .77; Specificity = .95; Youden’s index = .72; Proportion of agreement = .93, and Kappa coefficient = .65, p < .001. Among adolescents for accelerometry-measured total daily steps the 11,000 for males and 10,500 for females cut-off points should be used. For population guidelines regarding health-enhancing steps in adolescents, the cut-off point of 10,000 daily steps seems to be the most appropriate. Resumen. El propósito principal del presente estudio fue comparar la precisión de los umbrales de pasos diarios totales asociados a la recomendación de 60 minutos por día de actividad física moderada-vigorosa en adolescentes. Un total de 156 adolescentes, 87 varones y 69 mujeres, participaron en el presente estudio. La actividad física moderada-vigorosa y pasos se evaluaron objetivamente con acelerómetros GT3X durante ocho días consecutivos. Se calculó la precisión de los siguientes umbrales de pasos diarios totales (varones/mujeres): 9.930, 11.714, 12.000, 11.000/10.500, 14.000/11.500, 13.000/12.000, 8.500/7.500, 11.500/9.000, 10.500/9.500, 12.118, 12.118/12.605 y 10.000. Los resultados de precisión para los puntos de corte de los pasos diarios ajustados y no ajustados variaron de bajo a alto. Para los pasos diarios no ajustados, los puntos de corte 11.000 para los varones y 10.500 para las mujeres mostraron los mejores resultados: Sensibilidad= 0,85; Especificidad= 0,94; Índice de Youden= 0,78; Proporción de acuerdo= 0,93, y coeficiente de Kappa= 0,67, p < 0,001. Para los pasos diarios ajustados, el puntaje de corte de 10.000 mostró los mejores resultados: Sensibilidad= 0,77; Especificidad= 0,95; Índice de Youden= 0,72; Proporción de acuerdo= 0,93, y coeficiente de Kappa= 0,65, p < 0,001. Entre los adolescentes para los pasos diarios totales medidos con acelerometría se deberían utilizar los puntos de corte 11.000 para los varones y 10.500 para las mujeres. Para las recomendaciones a nivel poblacional sobre los pasos relacionados con la salud en los adolescentes, el punto de corte de 10.000 pasos diarios parece ser el más apropiado.